2022
DOI: 10.55493/5019.v11i3.4610
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Learning Habits with Students' English Learning Achievement at Vocational High School

Abstract: This study aimed to find the extent of the correlation between learning habits with students' English learning achievement. The research sample was taken from students in third grade of multimedia class, which consisted of 40 students. SPSS v25.0 was used for analyzing the data. A correlation test was carried out that yielded r-count value of 0.414 whereas, the value of r-table at significant 5% with N= 40 was 0.312. It thus proved that the value of data analysis was greater than the R table value, which accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As explained by the researchers (Ronimus et al, 2019;Berry, 2021;Barcomb & Cardoso, 2020;Yürük, 2020) stated in their study that experimental group showed significant improvements in pronunciation skill than the control group which showed higher cognitive engagement. Additionally, the researchers go on to point out that usage of digital games as a learning media can maximizes the language learning which will help to assist students' reading comprehension skill in English learning (Marsa et al, 2021;Pahamzah et al, 2020;Tan et al, 2019;Korkmaz & Öz, 2021). According to Marsa et al (2021); Tan et al (2019), they disputed that instead of hardcopy materials, the learners were more likely reading on the mobile platform.…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%
See 2 more Smart Citations
“…As explained by the researchers (Ronimus et al, 2019;Berry, 2021;Barcomb & Cardoso, 2020;Yürük, 2020) stated in their study that experimental group showed significant improvements in pronunciation skill than the control group which showed higher cognitive engagement. Additionally, the researchers go on to point out that usage of digital games as a learning media can maximizes the language learning which will help to assist students' reading comprehension skill in English learning (Marsa et al, 2021;Pahamzah et al, 2020;Tan et al, 2019;Korkmaz & Öz, 2021). According to Marsa et al (2021); Tan et al (2019), they disputed that instead of hardcopy materials, the learners were more likely reading on the mobile platform.…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%
“…Thus, DGBELL focuses on vocabulary as one of the competencies. A number of 12 studies conducted to identify the effects of digital games in improving the English vocabulary acquisition (Chen & Hsu, 2019;Chandra & Kepirianto, 2021;Sagubay-Lozarito & Segumpan, 2022;Padar, 2022;Vásquez & Ovalle, 2019;Pahamzah et al, 2020;Tan et al, 2019;Guaqueta & Castro-Garces, 2018;Vélez-Agosto & Rivas-Vélez, 2018;Hazar, 2020). Based on the study by Vásquez and Ovalle ( 2019), an evaluation of the findings acquired from the vocabulary assessment, learners' and educators' records revealed that following the intervention of a digital game on English vocabulary, the learners could acquire a considerable amount of vocabulary.…”
Section: Impacts Of Dgbell In Regard To Cognition Outcomes (Language ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inference is skill to predict outcome, main idea, implicit information, and cause-effect relationship in the text. MALL integrated with Quizizz improves students' reading comprehension (Pahamzah et al, 2020;Rasyid et al, 2021). Students' abilities in finding main idea of a text and understanding vocabularies is increased.…”
Section: Mall Improves Students' Reading Comprehensionmentioning
confidence: 99%
“…Consequently, students and educators no longer feel burdened (Zuhriyah & Pratolo, 2020). In teaching reading skills, Pahamzah, Syafrizal, Juniardi & Sukaenah, (2020) reported that the use of Quizizz as a learning media for reading comprehension is very good as students feel the ease of learning, especially in understanding a text. They become interested in reading and understanding because of the interesting features where it stimulates students to get the best score.…”
Section: Introductionmentioning
confidence: 99%